Logistics service provider–client relationships - So, Meko; Panayides, Photis (My University, 2005)
The paper investigates the effects of relationship orientation in the logistics service provider-client interaction. A conceptual model is developed and six research hypotheses are empirically analysed using structural equation modelling. The results indicate that relationship orientation has a positive influence on key organisational capabilities, like organisational learning and innovation, promoting an improvement in supply chain effectiveness and performance. Theoretical, managerial and research implications are discussed
Keywords: Transportation research; Logistics; Relationship marketing; Shipping